Side effect of deferiprone as iron chelator in patient with thalassemia - Mikhael Yosia; Pustika Amalia Wahidiyat (Indonesian Pediatric Society, 2017)
Background There are currently three available iron chelators: deferoxamine (DFO), deferasirox (DFX) and deferiprone (DFP). In Dr. Cipto Mangunkusumo Hospital and Indonesia, in general, the accessibility of DFP for thalassemia patients has been adequate. Even though its efficacy in removing iron has been proven by countless studies, questions relating to its safety and possible side effects continue to be raised. Objective To assess common side effects of DFP usage by an intensive literature search and compare them to that in a pediatric thalassemia patient, in order to determine if the child's symptoms in the were potentially caused by DFP. Methods A literature search using MeSH terms was done in PubMed. Full copies of articles that fulfil the inclusion criteria, based on their title, abstract, and subject descriptors, were critically appraised using The Joanna Brigs Institute (JBI) critical appraisal tools. Results A total of 10 research articles from 1998-2013 were deemed applicable to this study including: 2 case reports, 5 prospective cohort studies, 2 retrospective cohort studies, and 1 randomized control trial with a grand total of 1,026 samples. Conclusion Side effects of DFP include: neutropenia, agranulocytosis, increased ALT, gastrointestinal problems, arthralgia or arthropathy, increased appetite or weight, thrombocytopenia, urine discoloration, as well as auditory and visual disturbances. Our case report patient's symptoms of gum bleeding and haemorrhagic mass are not related to her DFP consumption.